Bacterial seed endophyte shapes disease resistance in rice - Matsumoto, Haruna; Fan, Xiaoyan; Wang, Yue; Kusstatscher, Peter; Duan, Jie; Wu, Sanling; Chen, Sunlu; Qiao, Kun; Wang, Yiling; Ma, Bin; Zhu, Guonian; Hashidoko, Yasuyuki; et al. (Nature plants, 2021)
Cereal crop production is severely affected by seed-borne bacterial diseases across the world. Locally occurring disease resistance in various crops remains elusive. Here, we have observed that rice plants of the same cultivar can be differentiated into disease-resistant and susceptible phenotypes under the same pathogen pressure. Following the identification of a seed-endophytic bacterium as the resistance-conferring agent, integration of high-throughput data, gene mutagenesis and molecular interaction assays facilitated the discovery of the underlying mode of action. Sphingomonas melonis that is accumulated and transmitted across generations in disease-resistant rice seeds confers resistance to disease-susceptible phenotypes by producing anthranilic acid. Without affecting cell growth, anthranilic acid interferes with the sigma factor RpoS of the seed-borne pathogen Burkholderia plantarii , probably leading to impairment of upstream cascades that are required for virulence factor biosynthesis. The overall findings highlight the hidden role of seed endophytes in the phytopathology paradigm of ‘disease triangles’, which encompass the plant, pathogens and environmental conditions. These insights are potentially exploitable for modern crop cultivation threatened by globally widespread bacterial diseases. In rice, one endophyte ( Sphingomonas melonis ) colonizes seeds and produces anthranilic acid, which confers resistance to a bacterial pathogen ( Burkholderia plantarii ) in the plant.